PROSES PENYUSUNAN ANGGARAN BERBASIS KINERJA DINAS KESEHATAN KABUPATEN KETAPANG - B61110065, FAINI RASYIDA (Jurnal Ekonomi Daerah (JEDA), 2014)
ABSTRACT The proposition of work plans and budgets of Health Departemen in allocating cost based on the amount of budget in the current or previous year added with certain percentage is not based on the standart expenditure and standart costs and it still has a program which overlaps resulting in waste costs.. This study aims to determine the process of performance-based budgeting at Health Departemen of Ketapang Regency This a qualitative study using case design. The staudy was conducted at analysis unit of Health Departemen of Ketapang regency. The variables of this study are service planning team,,executive and legislative budget team, the compentence of budget planners, the duties and function, the strategic plan, the annual working plan,public policy, interim budget priorities and funding ceilings of local government budget or PPAS APBD , standart analysis of expenditure, and work plans and budget or RKA/ Budget implementation document or DPA . This stady used in – depeth interview, open questioner and triangulation techniques for collecting data The proposition of plan and budgets has not involved the entire budget planners yet due to lack of the competence of human resources,particularly in terms of technical matter. The compostion of work plans and budget in relation to determining the amount of costs has not been based on standard expenditure analysis resulting in the remains of 2007 budget. The component of duties and function are not entirely included in annual strategic plans/work plans. The program/actinities in strategic plans/ work plans are not in accordance with RKA/DPA of 2008. The quality of public policy and PPAS APBD is consistent to program/acivities in RKA/DPA of year 2008. The time realization of the use of 2008 budget is accurate and it is accordance with the regulation of home affair minister or Permandagri number 13 year 2006 The proposition of RKA has not involved the entire budget planners. There is lack of competence of human resources, particularly in terms of technical side. The component of the duties and functions has not entirely been included in annual strategic plans/ work plans are not in accordance with RKA/ DPA year 2008. The qualityof public policy and PPAS APBD in health is accordance with RKA/DPA year 2008. The time reazlization of the use of 2008 budget is accurate and it is accordance with the regulation of home affair minister or permendagri Number 13 year 2006